2010
DOI: 10.1590/s1516-84842010000500010
|View full text |Cite
|
Sign up to set email alerts
|

Morbimortalidade em doença falciforme

Abstract: The high morbidity-mortality rates in sickle cell disease (SCD) led us to study the epidemiological profile and respective clinical complications of patients seen at a Regional Blood Center (HR) and a University Clinical Hospital (HC-U) between 1998 and 2007. In a retrospective study, 151 patients were evaluated regarding age, gender, skin color, origin, diagnosis, reason of visit to HR or reason and length of stay in the HC-U, and cause and age in cases of death. Simple descriptive statistical analysis was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
1
22

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 19 publications
5
19
1
22
Order By: Relevance
“…However, there is a risk of infections by viruses, bacteria and parasites with transfusions once serological screening is not compulsory for all microorganisms [10, 17, 18, 3032]. Despite the lack of data on blood transfusions performed in the individuals analyzed in the current study, we should consider this risk, and more detailed studies should be performed to verify the possible transmission of pathological agents in blood transfusions.…”
Section: Discussionmentioning
confidence: 98%
“…However, there is a risk of infections by viruses, bacteria and parasites with transfusions once serological screening is not compulsory for all microorganisms [10, 17, 18, 3032]. Despite the lack of data on blood transfusions performed in the individuals analyzed in the current study, we should consider this risk, and more detailed studies should be performed to verify the possible transmission of pathological agents in blood transfusions.…”
Section: Discussionmentioning
confidence: 98%
“…The results demonstrated that 100% of the subjects experienced pain on at least one body region in the previous 12 months and 81.5% in the previous seven days. A previous study also conducted in the same recruitment site (HRU) 25 showed that the most prevalent cause of health care consultation (64.4%) were pain crises.…”
Section: Discussionmentioning
confidence: 94%
“…Destaca-se ainda que a procedência da clientela das regiões NorteNoroeste (38%) do Estado do Paraná, pode ser explicada historicamente devido ao maior grau de miscigenação africana existente nessas regiões (7,9) . A grande maioria dos pacientes foi acompanhada periodicamente no ambulatório por três anos ou mais, o que pressupõe acompanhamento regular, orientações preventivas, contribuindo para melhor qualidade de vida e, por conseguinte menor índice de mortalidade, principalmente por problemas infecciosos em crianças menores de cinco anos, como evidenciado em outras pesquisas (9,20) . A crise álgica como evento clínico mais dramático da AF, causada pela oclusão microvascular com subsequente lesão tecidual, em resposta ao afoiçamento das hemácias, representou a complicação clínica mais frequente neste estudo e também a principal causa de internações hospitalares.…”
Section: Discussionunclassified
“…Ocorre geralmente em decorrência da isquemia tecidual e liberação de pirógenos endógenos; secundária às crises de anemia hemolítica ou como sinal de infecção. As infecções recorrentes, como a segunda maior complicação clínica, se justifica pela disfunção esplênica, resultante da perda da função retículo-endotelial do baço, em consequência dos recorrentes infartos esplênicos, favorecidos pela microvascularização deste órgão, precipitando o processo de falcização, e com isso a hipóxia tecidual (10,20) . Alguns achados clínicos presentes na clientela assistida -êmese, diarréia, linfonodomegalia, dispnéia, tosse e coriza hialina -podem reafirmar a recorrência desses processos infecciosos.…”
Section: Discussionunclassified